Exploring Value Co-Creation as a Driver of Consumer Engagement and Purchase Intention in Influencer Marketing - Adnanto Mujiibu Arif Hakeem; Yolanda Masnita; Kurniawati Kurniawati (Jurnal Cita Ekonomika, 2026)
This study examines the impact of influencers’ value co-creation behavior on consumer engagement and purchase intention through perceptual constructs. Using a between-subject experimental design, 200 Indonesian social media users were exposed to either a co-creation or control video stimulus. The co-creation condition featured influencers providing personal insights and crea-tive usage of a product, while the control showed standard product infor-mation. Results indicate that co-creation content significantly enhances per-ceived product value but does not directly influence other perceptual con-structs or engagement. Mediation analysis found that perceived expertise, favorability, benevolence, and source likeability predict engagement, but are not directly triggered by content type. Engagement itself strongly predicts purchase intention. These findings suggest that while co-creation can improve product perceptions, it is not sufficient alone to drive engagement or purchase decisions. Practical implications highlight the importance of combining co-creation with authenticity and credibility to effectively influence consumer behavior in digital contexts.